Improving cyclic stability of lithium cobalt oxide based lithium ion battery at high voltage by using trimethylboroxine as an electrolyte additive. (10th August 2015) - Wang, Xianshu; Xing, Lidan; Liao, Xiaolin; Chen, Xiaofen; Huang, Wenna; Yu, Qipeng; Xu, Mengqing; Huang, Qiming; Li, Weishan
Highlights: TMB is effective as electrolyte additive for improving cyclic stability of high voltage LiCoO2 /graphite battery. TMB is oxidized preferentially to electrolyte, forming a compact and thin protective film on LiCoO2 . This film protects LiCoO2 from destruction and suppresses electrolyte decomposition. Abstract: Trimethylboroxine (TMB) is used as electrolyte additive to improve the cyclic stability of LiCoO2 /graphite full cell under high voltage. It is found that capacity retention of LiCoO2 /graphite cell at 0.3C rate after 200 cycles between 3.0 ∼ 4.5 V is improved from 29 % to 66 % by applying 0.5 % (by weight) TMB in EC-based electrolyte. Charge-discharge tests on graphite/Li and LiCoO2 /Li half cells demonstrate that the improvement in cyclic stability of the full cell results from the contribution of TMB to the enforced stability of LiCoO2 cathode. Cyclic voltammogram shows that TMB is oxidized preferentially to the EC-based electrolyte, while physical characterizations, from SEM, TEM, FTIR and XPS, indicate that TMB helps build a thin but protective film on LiCoO2, which improves the interfacial stability of high voltage electrode/electrolyte.